Phytochemical analysis and evaluation of skin irritation, acute and sub-acute toxicity of Cymbopogon citratus essential oil in mice and rabbits. (2019) - Lulekal, Ermias; Tesfaye, Solomon; Gebrechristos, Selam; Dires, Kassahun; Zenebe, Tizazu; Zegeye, Nigus; Feleke, Gezu; Kassahun, Abayneh; Shiferaw, Yoseph; Mekonnen, Awol
Graphical abstract: Highlights: C. citrates essential oil contains about 71.297 % citral. 10 % ointment formulation of C. citratus oils did not cause skin irritation. Oral LD50 of C. citratus essential oil was greater than 2000 mg/kg. C. citratus essential oil didn't produce any toxicity sign. No histopathological changes were detected in the organs tested. Abstract: Cymbopogon citratus has been used by the local people in Ankober district, northern Ethiopia, as traditional medicine to treat various ailments. Its essential oil has been shown to have antibacterial, antifungal, antiprotozoal, anti-carcinogenic, anti-inflammatory and antioxidant activities amongst others. This study was conducted to determine skin irritation, acute and subacute toxicity of C. citratus essential oil in mice and rabbits. The essential oil was analyzed using GC–MS. The essential oil at dose of 2000 mg/kg body weight was administered to mice for 21 consecutive days. The mice mortality, behavioral change, injury and other signs of illness were recorded once daily. Biochemical parameters were evaluated. Liver and kidney were taken after sacriﬁce for gross ﬁndings and histological analyses. 10 % ointment formulation of C. citratus oils was applied on the rabbit skin to determine skin irritation effects. The result revealed, the presence of citral (71.297%), myrcene (19.034%), 4, 5-epoxycarene (2.780%), linalool (1.713%), ((S)-cis-verbenol (1.110 %), linalool (1.713 %), (( S )-cis-verbenol (1.110 %) and undecan-2-one (1.001 %) in the C . citratus essential oil. There was no signiﬁcant difference (p > 0.05) in the body weights, gross abnormalities of the organs and biochemical parameters compared to the control. No histopathological changes were detected in the organs tested. 10 % ointment formulation of C. citratus oils did not cause skin irritation. Analysis of results leads to the conclusion that Ethiopian C. citratus essential oil may be considered as relatively safe and non-toxic.